The crystal structure of phenantroline-κ2 N,N′-bis(6-phenylpyridine-2-carboxylato-κ2 N,O)copper(II), C36H24N4O4Cu - Mei-Li Zhao; Xi-Shi Tai (Zeitschrift für Kristallographie - New Crystal Structures)
C36H24N4O4Cu, monoclinic, I12/a1 (no. 15), a = 16.5119(17) Å, b = 11.0747(7) Å, c = 17.6272(17) Å, β = 117.916(13)°, V = 2848.3(5) Å3, Z = 4, R gt(F) = 0.0335, wR ref(F 2) = 0.0759, T = 200 K.